ASUHAN KEBIDANAN PADA IBU NIFAS Ny ”A” P2A0H2 DI KLINIK UTAMA NILAM SARI TEMBILAHAN TAHUN 2019 - Laylis Shofyati; Nurul Indah Sari (STIKES HUSADA GEMILANG, 2021)
The postpartum period is a period that starts from 2 hours after the birth of the placenta up to 6 weeks after that. The most important thing in the puerperium is the evaluation of the occurrence of bleeding, because postpartum bleeding can cause postpartum maternal death. Complete postpartum coverage in Indragiri Hilir was 73.5%. Data on postpartum mothers at the Nilam Sari Tembilahan Main Clinic in 2019 as many as 124 people. The care is held from June 24 to August 03, 2019. The purpose of midwifery care is to be able to provide midwifery care to Mrs.